A Novel Disease (Water Bubble Disease) of the Giant Freshwater Prawn Macrobrachium rosenbergii Caused by Citrobacter freundii: Antibiotic Treatment and Effects on the Antioxidant Enzyme Activity and Immune Responses - Caiyuan Zhao; Huagen Wen; Shengsheng Huang; Shaoping Weng; Jianguo He (Antioxidants, 2022)
The giant freshwater prawn, Macrobrachium rosenbergii, is an important and economical aquaculture species widely farmed in tropical and subtropical areas of the world. A new disease, “water bubble disease (WBD)”, has emerged and resulted in a large loss of M. rosenbergii cultured in China. A water bubble with a diameter of about 7 mm under the carapace represents the main clinical sign of diseased prawns. In the present study, Citrobacter freundii was isolated and identified from the water bubble. The optimum temperature, pH, and salinity of the C. freundii were 32 °C, 6, and 1%, respectively. A challenging experiment showed that C. freundii caused the same typical signs of WBD in prawns. Median lethal dose of the C. freundii to prawn was 104.94 CFU/g. According to the antibiogram tests of C. freundii, florfenicol and ofloxacin were selected to evaluate their therapeutic effects against C. freundii in prawn. After the challenge with C. freundii, 86.67% and 72.22% survival of protective effects against C. freundii were evaluated in the oral florfenicol pellets and oral ofloxacin pellets feding prawns, respectively, whereas the mortality of prawns without fed antibiotics was 93%. After antibiotic treatment and C. freundii infection, the activities of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), glutathione S-transferase (GST), malondialdehyde (MDA), acid phosphatase (ACP), alkaline phosphatase (ALP), and lysozyme (LZM) in the hemolymph and hepatopancreas of the prawns and the immune-related gene expression levels of Cu/Zn-SOD, CAT, GPx, GST, LZM, ACP, anti-lipopolysaccharide factor, crustin, cyclophilin A, and C-type lectin in hepatopancreas were all significantly changed, indicating that innate immune responses were induced by C. freundii. These results can be beneficial for the prevention and control of C. freundii in prawns.